Preparing work‐ready sonography trainees: An accelerated model of ultrasound training by the University of Auckland. Issue 4 (15th November 2016) - Sim, J.
Abstract: Introduction: New Zealand is experiencing a national shortage of sonographers. The intense nature of clinical supervision negatively impacts on supervisor and workplace productivity thereby further exacerbating the workforce shortage. The University of Auckland piloted a new education initiative to prepare sonography trainees to be more 'work ready' and to reduce supervision burden of sonographers. Methods: Trainees attended a 12‐week intensive course on campus full time. The course focused on building sonographer core competencies, placing equal emphasis on the development of critical thinking and psychomotor skill of ultrasound scanning. An independent evaluator was appointed to determine the quality of the course and the impact of the trainees on supervision burden and workplace productivity. Results: Trainees were reported to be 6 to 9 months ahead of students who did not undergo the 12‐week intensive course. The clinical supervision burden was reduced without compromising on quality of clinical practice. Discussion: This new education initiative represents a departure from the traditional model by having trainees to commence their initial training full time at the university. With the successful conclusion of the pilot study, both public and private sectors currently jointly contribute to the funding of the intensive course.